Dynamic modeling of vehicle populations: An engineering approach for emissions calculations - Zachariadis, Theodoros; Samaras, Zissis; Zierock, Karl Heinz (My University, 1995)
A model initially developed for forecasts of air pollutant emissions from motor vehicles is presented, with special emphasis on its vehicle dynamics module. Vehicle density forecasts are performed separately for passenger cars, trucks, buses, and motorcycles. Combined with estimates of vehicle usage parameters they are used to predict the total traffic volume up to the year 2010. The internal turnover of the vehicle fleet is simulated with a modified Weibull function, and the technology substitution process is determined nonanalytically. Although more refined approaches have been developed for the prediction of the dynamic behavior of car populations, the one presented here has been designed in such a way that it can be applied to countries where detailed information is lacking or too difficult to find, and even nonexperts can implement it reasonably well.
Keywords: Air pollution; Calculations; Dynamics; Air pollutant emissions; Motorcycles; Vehicles